Enhancing thermal energy storage: Investigating the use of graphene nanoplatelets in phase change materials for sustainable applications - Muppana, Veera Nagendra; Arif Fikri, Rosli; Samykano, Mahendran; Kousik Suraparaju, Subbarama; Reji Kumar, R.; Wan Azmi, Wan Hamzah (Wiley-Blackwell, 2024)
The adoption of phase change materials (PCMs) for thermal energy storage in low- and medium-temperature settings is witnessing a notable surge. However, the lesser thermal conductivity (TC) poses a noteworthy challenge to PCM's heat transfer and storage capabilities. One of the noteworthy solutions to augment the TC is incorporating nanoparticles in the PCM. Nevertheless, nanoparticles often clump together after several cycles due to poor compatibility and weak interfacial strength. Functionalization methods have been proposed to address this issue, offering improved performance for energy storage applications. Herein, graphene nanoplatelets (GNP) and functionalized graphene nanoplatelets (FGNP) are dispersed into A70 PCM at mass fractions ranging from 0.1 to 1.0 wt% using two-step method. Fourier transform infrared analysis confirms the successful integration of FGNP into A70 PCM without altering its chemical characteristics. Adding 1.0 wt% FGNP to A70 PCM increases its TC by 140.88%, with just a 3.02% decrease in latent heat enthalpy. However, incorporating pure GNP (1.0 wt%) improves TC by 48.83%. The engineered nano-PCMs exhibit robust thermal and chemical stability even after undergoing 1000 thermal cycles, remaining unchanged up to 414.64 °C. This exceptional stability makes the formulated nanoenhanced PCM suitable for sustainable thermal applications.